Advanced Concepts, Methodologies and Technologies for Transportation and Logistics - Żak, Jacek; Hadas, Yuval; Rossi, Riccardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is a collection of original papers produced by the members of the Euro Working Group on Transportation (EWGT) in the last several years (2015-2017). The respective chapters present the results of various research projects carried out by the members of the EWGT and extended versions of presentations given at the last several meetings of the EWGT. The book offers a representative sampling of the EWGT's research activities and covers the state-of-the-art in quantitative oriented transportation/logistics research. It highlights a range of advanced concepts, methodologies and technologies, divided into four major thematic streams: Multiple Criteria Analysis in Transportation and Logistics; Urban Transportation and City Logistics; Road Safety and Artificial Intelligence and Soft Computingin Transportation and Logistics. The book is intended for academics/researchers, analysts, business consultants, and graduate students who are interested in advanced techniques of mathematical modeling and computational procedures applied in transportation and logistics.
Keywords: Computational intelligence; Artificial intelligence; Industrial Management; Computational Intelligence; Artificial Intelligence; Industrial Management